Bezetting directiekamer. Achter bureau (met armen over elkaar) directeur Lugard. Serie van twee foto's - Wingerde, G. van
Bezetting directiekamer. Achter bureau (met armen over elkaar) directeur Lugard. Serie van twee foto's.